SEX-TYPING IN DAVID EBERSHOFF’S THE DANISH GIRL - AHMAD HIBATULLAH HAQQY (LITERA KULTURA : Journal of Literary and Cultural Studies, 2019)
David Ebershoff’s The Danish Girl is a novel about a transgender in America. The objective of this research is to find out the depiction and the reasons of sex-typing process in The Danish Girl novel’s main character. This study used the Psychoanalysis theory by Paul Henry Mussen. In this study, there is two problem formulation. The first is to reveal how sex-typing depicted David Ebershoff’s The Danish Girl. The second problem is the reasons for the habit of sex-typing in David Ebershoff’s The Danish Girl. After analyzing this novel, there are two conclusions. Firstly, Einar Wegener is described as a man who has a feminine tendency. He identifies himself as a girl who trapped inside a male body. Secondly, Einar fill up the reasons for the occurrence of sex-typing habit. The reasons split into three parts. Firstly, the researcher finds that Einar get through the identification process. The second is a desire for praise, affection, and acceptance by parents and peers for sexually proper behaviour. The last, fear of punishment or rejection for sexual misconduct. Nevertheless, Einar turns out to be a woman trapped in a mans body. Keywords: Sex-typing, Psychoanalysis, Transgender, Transsexual